Reliability of aerobic and anaerobic field tests in in measuring athletes` performances: A statistical approach on a cohort of 100 subjects - Cusano, P.; Ascione, A.; Mezzapesa, G. N. (Journal of Human Sport & Exercise, 2019)
To determine the statistical relationships among different consolidated performance tests (Yo-Yo, jump, sprint and agility), and the Powersprint™ device, an isotonic equipment, usually used to increase the muscular strength of athletes, used here as performance test. One hundred individuals were involved in the tests (16 females and 84 males). Ninety-five subjects were practicing different field sports, whereas 3 female and 2 male subjects were inactive. Gender, height and body mass were recorded. Participants completed the following tests: Squat Jump, Counter Movement Jump, 10 m sprint, 15 m sprint, Change of Direction, Yo-Yo Intermittent Recovery Test level 1 and PowerSprint 3.0™. Results of this experiment highlighted that PowerSprint 3.0™ is positively and significantly correlated with Squat Jump, Counter Movement Jump, 10 m sprint, 15 m sprint, Change of Direction, Yo-Yo Intermittent Recovery Test level 1. Additionally, the principal component analysis, as expected, was able to neatly differentiates between male, female and inactive subjects. The selected tests appeared particularly effective in giving information about athlete performances in soccer. Performances measured with the PowerSprint 3.0™ positively and significantly correlated with jumps, COD, sprint and YYIR1 tests. This is an indication of the possible use of this light, inexpensive and portable instrument for measuring athlete performances and checking the effectiveness of training programs.